Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.1 - Radicals and Radical Functions - Exercise Set: 79

Answer

-1

Work Step by Step

We are given that $g(x)=\sqrt[3] (x-8)$. Therefore, $g(7)=\sqrt[3] (7-8)=\sqrt[3] (-1)=-1$ We know this, because $(-1)^{3}=-1\times-1\times-1=-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.